2008
DOI: 10.1111/j.1574-6968.2008.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of diverse genes for class 1 integron-integrases from environmental DNA samples

Abstract: Class 1 integrons are an important vector for the spread of antibiotic resistance. The core of this genetic element is highly conserved in all class 1 integrons recovered from clinical contexts. Recently, bacteria containing more divergent class 1 integrons have been isolated from environmental samples, suggesting undiscovered diversity in these elements. We performed a culture-independent survey of the class 1 integron-integrase gene (intI1) from environmental DNA, assessing sequence variation using capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 30 publications
(37 reference statements)
3
55
0
Order By: Relevance
“…Although this correlation was not as strong as other study , the high abundance of intI1 and correlation with abundance of ARGs could suggest that intI1 may play certain role in the dissemination of ARGs, thus indicating that horizontal gene transfer could be an important pathway for ARG proliferation, especially under antibiotic selection pressure (Ochman et al, 2000). Previous study also demonstrated that class 1 integrons are an important vector for the propagation of antibiotic resistance (Gillings et al, 2008).…”
Section: Relationship Between Args and Environmental Factors Or Inti1mentioning
confidence: 54%
“…Although this correlation was not as strong as other study , the high abundance of intI1 and correlation with abundance of ARGs could suggest that intI1 may play certain role in the dissemination of ARGs, thus indicating that horizontal gene transfer could be an important pathway for ARG proliferation, especially under antibiotic selection pressure (Ochman et al, 2000). Previous study also demonstrated that class 1 integrons are an important vector for the propagation of antibiotic resistance (Gillings et al, 2008).…”
Section: Relationship Between Args and Environmental Factors Or Inti1mentioning
confidence: 54%
“…5). Examination of metagenomic DNA recovers diverse class 1 integron integrase genes, many with less than 95% nucleotide sequence identity (127). In contrast, the integron integrase genes in all class 1 integrons from clinical sources are essentially identical, strongly suggesting that all clinical class 1 integrons are recent descendants of a single event involving just one representative of the diverse intI1 sequence variants present in natural environments.…”
Section: Origin Of Class 1 Integrons As Vectors For Antibiotic Resistmentioning
confidence: 99%
“…These chromosomal integrons carry gene cassettes of unknown function and exhibit significant sequence diversity in their IntI1 genes (30,34,127). All chromosomal class 1 integrons characterized from environmental sources have common terminal sequences.…”
Section: Origin Of Class 1 Integrons As Vectors For Antibiotic Resistmentioning
confidence: 99%
“…Samples included stream sediments from Cowan Creek, North Turramurra (RA: Hardwick et al, 2008), biofilms from Mars Creek, North Ryde (BF: Gillings et al, 2008b), contaminated soil from Balmain (BAL; Yeates and Gillings, 1998), biofilms from a groundwater treatment plant in Botany (OR: Gillings et al, 2006) This element carries the terminal inverted repeats (IRi and IRt), a class 1 integron integrase gene (intI1), a primary recombination site (attI; small diamond), a cassette array (usually encoding antibiotic resistance) with each cassette bounded by secondary recombination sites (attC; circles), a cassette for quaternary ammonium compound resistance (qacE) and a transposition module (tni). (b) An environmental class 1 integron embedded into a bacterial chromosome carries the integrase gene, flanking regions and a cassette array that does not usually encode antibiotic resistance.…”
Section: Methodsmentioning
confidence: 99%